Mechanisms of Action of Ozone Therapy in Emerging Viral Diseases: Immunomodulatory Effects and Therapeutic Advantages With Reference to SARS-CoV-2 - Cenci, Alessandra; Macchia, Iole; La Sorsa, Valentina; Sbarigia, Clemente; Di Donna, Valentina; Pietraforte, Donatella (Frontiers in Microbiology, 2022)
Medical oxygen-ozone (O2-O3) is a successful therapeutic approach accounting on the assessed beneficial action of ozone in the range 30-45 μg/ml (expanded range 10-80 μg/ml according to different protocols), as in this dosage range ozone is able to trigger a cellular hormetic response via the modulating activity of reactive oxygen species (ROS), as signaling molecules. The ozone-dependent ROS-mediated fatty acid oxidation leads to the formation of lipid ozonization products (LOPs), which act as signal transducers by triggering ROS signaling and therefore mitohormetic processes. These processes ultimately activate survival mechanisms at a cellular level, such as the Nrf2/Keap1/ARE system activation, the AMPK/FOXO/mTOR/Sir1 pathway and the Nrf2/NF-kB cross talk. Furthermore, indirectly, via these pathways, LOPs trigger the HIF-1α pathway, the HO-1 signaling and the NO/iNOS biochemical machinery. Ozone-driven shift of cytokine activation pathways, from pro-inflammatory to anti-inflammatory immediately afterwards, also exert direct immunoregulatory effects on regulatory T lymphocytes as well as on the intestinal microbiota, which in turn can affect immune response thus influencing the progression of the disease. In this review, we will describe the biological and biochemical mechanisms of action of ozone therapy with the aim of evaluating both positive and critical aspects of ozone use as a therapeutic adjuvant in the light of emerging viral infections, such as SARS-CoV-2 and microbiome associated disorders related to SARS-CoV-2.